Comprehensive Analysis of Histamine-2 Receptor Antagonists on Dementia Risk: A Systematic Review of Cohort Studies - Yong, Yee Wen; Puspitasari, Vivien (Acta Neurologica Indonesia, 2025)
Introduction : Histamine-2 Receptor Antagonist (H2RA) are widely used to manage upper gastrointestinal diseases (UGID). However, growing concerns have emerged regarding their potential neurocognitive side effect, particularly an increased dementia risk. H2RAs are often preferred over proton pump inhibitors (PPIs) for enhanced therapeutic efficacy in clinical settings. Material and methods : This research adhered to the PRISMA guidelines to select studies and assess biases. Databases (PubMed, Scopus, and Cochrane) are systematically searched from 2020-2025, and available studies are further evaluated for eligibility and risk of bias using the Cochrane risk of bias assessment tools for non-randomized studies of interventions (ROBINS-I). Discussion : Six studies were analyzed, with four cohort studies showing no significant association between H2RA use and dementia risk. However, H2RA use was associated with accelerated cognitive decline in patients with mild cognitive impairment (MCI) and Alzheimer’s disease (AD). The anticholinergic effects of H2RAs may contribute to cognitive impairment by disrupting histamine's role in the central nervous system and vitamin B12 absorption. However, the pathophysiological mechanisms remain unclear and the findings across studies are inconsistent. Further randomized controlled trials (RCTs) with larger sample sizes are needed to elucidate the potential long-term effects of H2RAs on cognitive health. Conclusion : This systematic review found no clear association between H2RA use and an increased risk of dementia, but noted accelerated cognitive decline in MCI and AD patients. Keywords: alzheimer’s disease; cognitive impairment; dementia; gastric acid-suppressive agents; histamine-2 receptor antagonists